Problems and Development Strategies of Sharia Pawntown in Indonesia: Analysis of Systematic Literature Review - Akhmad Hulaify; Muhammad Sodiki; Iman Setya Budi; Zakiyah Yoenani; Rozzana Erziaty (Faculty of Law, Universitas Pekalongan, 2022)
The development of sharia pawnshop institutions is like mushrooms in the rainy season, in tune with the development of conventional pawnshops even though the quantity of network offices, customers, turnover and profits is still not large. However, at least the development is worth considering, especially with the existence of management policies in several areas, all of the conventional pawnshop network offices have been converted into Sharia Pegadaian network offices. This research is a systematic literature review study which aims to find out the extent of a thorough study regarding the Problems and Strategies for Development of Islamic Pawnshops in Indonesia by focusing on the preparation of journals, final assignments such as theses, theses, and dissertations. The method used consists of three stages, namely collection, assessment, and presentation. The results of this study indicate that in the last 18 years 55 studies have been written related to sharia pawnshops but related to the study of Problems and Strategies for Development of Sharia Pawnshops in Indonesia after sorting according to the appropriate researcher only 15 studies, both journals and final assignments related to Problems and Strategies Development of Islamic Pawnshops in Indonesia. In terms of theme, the issue related to